PENGARUH ANGKA HARAPAN HIDUP DAN HARAPAN LAMA SEKOLAH TERHADAP INDEKS PEMBANGUNAN MANUSIA - Dastanta irvan Ginting; Irsad Lubis (Bisnis-Net, 2023)
This research aims to investigate the influence of life expectancy and years of schooling on the Human Development Index (HDI) in Langkat Regency. The research findings indicate a positive correlation between life expectancy and HDI, affirming that an increase in life expectancy correlates with an improvement in HDI. This phenomenon reflects the positive impact of enhanced community health on overall human development. Furthermore, years of schooling have also been proven to play a crucial role in shaping HDI. The analysis results demonstrate that communities with higher years of schooling tend to have a higher HDI. This illustrates a close relationship between investment in formal education and the enhancement of human development levels. The research contributes valuable insights into the factors that drive sustainable human development in the context of Langkat Regency.Keywords : Life Expectancy, Years of Schooling, Human Development Index